1999
DOI: 10.1162/089892999563283
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Endogenous and Exogenous Spatial Orienting: A Functional MRI Study

Abstract: Whole-brain functional magnetic resonance imaging (MRI) was used to examine the neural substrates of internally (endogenous) and externally (exogenous) induced covert shifts of attention. Thirteen normal subjects performed three orienting conditions: endogenous (location of peripheral target predicted by a central arrow 80% of the time), exogenous (peripheral target preceded by noninformative central cue). Behavioral results indicated faster reaction times (RTs) for valid than for invalid trials for the endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
170
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(198 citation statements)
references
References 85 publications
21
170
1
6
Order By: Relevance
“…saccades toward the direction opposite to an abrupt-onset target [154]). Furthermore, a functional MRI study [155], employing the Posner RT paradigm to identify the brain areas involved in exogenous and endogenous orienting, demonstrated largely overlapping activations in the parietal and dorsal premotor regions for both modes of orienting, except for an activation in the right dorsolateral prefrontal cortex (BA 46), that was exclusive to the endogenous condition. One important aspect of endogenous orienting, that is, likely to be subsumed by frontal cortical areas is the inhibitory suppression of distractor activity [22].…”
Section: Impaired Exogenous Orienting In Unilateral Neglect: Implicatmentioning
confidence: 99%
“…saccades toward the direction opposite to an abrupt-onset target [154]). Furthermore, a functional MRI study [155], employing the Posner RT paradigm to identify the brain areas involved in exogenous and endogenous orienting, demonstrated largely overlapping activations in the parietal and dorsal premotor regions for both modes of orienting, except for an activation in the right dorsolateral prefrontal cortex (BA 46), that was exclusive to the endogenous condition. One important aspect of endogenous orienting, that is, likely to be subsumed by frontal cortical areas is the inhibitory suppression of distractor activity [22].…”
Section: Impaired Exogenous Orienting In Unilateral Neglect: Implicatmentioning
confidence: 99%
“…For instance, by setting a SOA at 100 or 150 ms, and using a peripheral cue, orienting would be automatic and would occur without volitional control, whereas at longer SOAs (e.g., 800 ms) a greater voluntary control on orienting would be required to maintain attention on the cued position (Epstein, Conners, Erhardt et al, 1997). Yet another important feature determining automatic or voluntary orienting seems to be set-validity, that is, the ratio between valid and invalid trials (Rosen, Rao, Caffarra et al, 1999). Automatic orienting is supposed to occur regardless of the validity of the cue, that is even when the cue is misleading.…”
Section: Introductionmentioning
confidence: 99%
“…Three of these studies found little or no differences between voluntary and involuntary conditions (Kim et al, 1999;Peelen et al, 2004;Rosen et al, 1999). Two studies found differences in parietal-frontal networks that probably mediate the control of attention (Kincade et al, 2005;Mayer et al, 2004).…”
mentioning
confidence: 98%
“…Several studies have used fMRI to compare voluntary and involuntary attention (Kim et al, 1999;Kincade, Abrams, Astafiev, Shulman, & Corbetta, 2005;Mayer, Dorflinger, Rao, & Seidenberg, 2004;Peelen, Heslenfeld, & Theeuwes, 2004;Rosen et al, 1999). Three of these studies found little or no differences between voluntary and involuntary conditions (Kim et al, 1999;Peelen et al, 2004;Rosen et al, 1999).…”
mentioning
confidence: 99%